The Study of Institutional and Political System Factors Affecting Changes in Educational Public Expenditure from 1998 to 2019 - Kingphuang, Phichitchai (King Prajadhipok’s Institute Journal, 2023)
This research article analyzes the effects of institutional and political system factors, compared with socioeconomic factors, on the adjustment in public expenditure on education in Thailand, using secondary data and time series data for 22 years from 1998 to 2019. The objective of the study is to observe the influence of institutional and political system factors on the changes in public expenditure on education, compared with that of socioeconomic environment factors from 1998 to 2019, and to propose policy recommendations that improve the allocation of public expenditures more focused on education development to reduce inequality and expand educational opportunities. The result of the study reveals that the influential socioeconomic factors on the change in public education expenditure, such as population, economic development (gross domestic product change rate), income inequality (Gini coefficient), and trade openness, are correlated with the public expenditure on education. On the other hand, institutional and political system factors inducing the changes in public education expenditure include gradual decision-making in bureaucracy—analyzing public education expenditures in the previous years, government efficiency, and political stability & absence of violence. The public education expenditure tends to gradually modify from the original due to changes in the demographic, gross domestic product change rate, and the Gini coefficient, which are socioeconomic factors that slowly shift and are difficult for the state to control. As a result, the allocation of public expenditure on education has altered slightly from the previous year. However, the country is a high level of inequality, so the significant shift in education expenditure requires changes in other factors. For instance, make use of the opportunities from trade openness to achieve economic growth that will be an indirect factor for the government in generating more revenue for expanding public services, along with supervision to ensure that government agencies operate efficiently so that the budget is used more effectively and efficiently, same as overseeing political stability and civil liberties for continuous development.